LANDASAN KONSEPTUAL OTONOMI DAERAH DALAM PERSPEKTIF ISLAM - Anwar, Ahmad Faridz (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
The configuration of Muslim society that was built by Rasulullah SAW and his friends in Medina, which deserves to be called an Islamic state, has become an example of truth that occupies the highest position after the Koran. The research method considered suitable for this writing is the descriptive qualitative method. The concept of regional autonomy in an Islamic perspective is Al-Imarah Al-Khashah and Al-Imarah Al-Ammah, each of which has duties and functions in carrying out government. The caliph as head of state gives authority to the al-amir (regional head), namely collecting taxes in the region, managing regional administration and providing services to the people in the region, maintaining security in the region, collecting kharaj and collecting zakat, upholding and spreading the Islamic religion in the region. , become a prayer leader.